Exploring the Determinants of Intention to Use P2P Mobile Payment in Spain. Issue 2 (3rd April 2021) - Liébana-Cabanillas, Francisco; Molinillo, Sebastian; Japutra, Arnold
ABSTRACT: Peer-to-peer (P2P) mobile payment is a mobile banking service with major growth potential. We contribute to the body of knowledge on technology adoption by proposing a conceptual model based on the theory of reasoned action, extended with additional mobile payment constructs identified in the literature review. The results show that usefulness, subjective norms, and personal innovativeness have a particularly strong, direct influence on intention to use.